Analysis of composite stiffener under successive impact and bending test. (September 2017) - Ridha, Muhammad; Tay, Tong-Earn; Werner, Sven; Joern, Paul; Tan, Vincent Beng Chye
In this article, we present the analysis, modelling and experimental investigation of composite omega stiffeners from non-penetrating impact to bending-after-impact. We used advanced computational methods to determine the extent of damage due to impact and, without many simplifications to the damage, predict the residual bending-after-impact strength under four-point-bend tests. The predicted sizes and patterns of impact damage, and the subsequent predicted bending strengths are compared to experimental tests of omega stiffeners. This work shows that preserving the details and fidelity of damage in the computational model is critical to successful prediction of residual strength. It was also found that modifying the design of the stiffeners by changing the orientation of some of the plies reduces the extent of impact damage and increases residual bending strength.